The real and the imagery in the building of the first stage of the republic of Colombia - Cuño Bonito, Justo (Universidad Pedagógica y Tecnológica de Colombia, 2011)
The present article a relection about how the history has been a improvement means of the elites in the Colombian society, in spite of the various processes of historic knowledge, this scenery is still alive. It seemed that the historians were not concerned for the incident that it has the knowledge in the conformation of an ideology of nation. This way they have centered the visions on the bicentenary that where there was not a deep relection to itself, but elements have tried to be contributed to disguise the social reality. In this vision is very important to analyze how the symbolic is used to reinforce the relationships of power. Thus, concepts like that of sovereignty that met materialized in the constitutions were focused on a small group that was fulilling certain requirements, which was stopping to a great number of excluded population, generating strong conlicts among the regional and local elites. The relections raised in this article are focused on analyzing how the population and particularly the popular sectors took part in the armies and in this way they have become active part in the construction of nation processes.